Pengaruh Usia, Pendidikan, dan Gender Terhadap Kualitas Tenaga Kerja di Destinasi Pariwisata Alam Kabupaten Pamekasan. - Solikha, Ulfatus; Wispandono, Raden Mas Mochammad (JURNAL ILMIAH EDUNOMIKA, 2024)
This research investigates the impact of age, education, and gender on workforce quality in Pamekasan Regency's natural tourism sector. The study uses a quantitative approach rooted in positivism, focusing on a specific sample from the tourism workforce population. Data were collected via questionnaires and analyzed statistically using SPSS to test hypotheses. Key tests, including validity, reliability, and classic assumption checks (normality, multicollinearity, and heteroskedasticity), ensured robust data quality. Regression analysis shows that age, education, and gender significantly and positively impact workforce quality. Specifically, age (tcount = 2.232, Sig = 0.029), education (tcount = 2.926, Sig = 0.005), and gender (tcount = 3.106, Sig = 0.003) all exhibit significant positive influences, as confirmed by F-test results (Fcount = 24.274, Sig = 0.000). These findings highlight the importance of demographic factors in enhancing workforce quality in Pamekasan's natural tourism sector.